Cell pH in the rat proximal convoluted tubule. Regulation by luminal and peritubular pH and sodium concentration. - Alpern, R J (1986)
To examine the relative roles of apical and basolateral membrane transport mechanisms in the regulation of cell pH in the proximal convoluted tubule, cell pH was measured in the in vivo microperfused rat tubule using fluorescence. Decreasing luminal pH by 0.7 pH units caused cell pH to decrease by 0.08 pH units, whereas a similar decrease in peritubular pH caused cell pH to decrease by 0.32 pH units. Inhibition of basolateral membrane bicarbonate transport with peritubular 4-acetamido-4'-isothiocyanostilbene-2,2'-disulfonate (SITS) enhanced the response to luminal fluid acidification. Removal of luminal sodium caused a small transient acidification which was followed by a late alkalinization. Peritubular SITS increased the magnitude of the transient acidification, and eliminated the late alkalinization. The acidification was partially inhibited by luminal amiloride. The results demonstrate sodium-coupled processes on both the apical (Na/H antiport) and basolateral (Na/HCO3 symport) membranes. Basolateral membrane transporters are more important determinants of cell pH.